Evaluation of safety and immunogenicity of duck-plague virus gC/gE double gene deletion - Ruan, Peilin; Feng, Xin; Cheng, Anchun; Wang, Mingshu; Zhang, Wei; Wu, Ying; Yang, Qiao; Tian, Bin; Ou, Xuming; Sun, Di; Zhang, Shaqiu; Mao, Sai; et al. (Frontiers in Immunology, 2022)
Duck plague caused by duck plague virus (DPV) is a highly contagious disease that can cause serious morbidity and death in waterfowl such as ducks and geese, and bring huge economic losses to the duck industry. In this study, on the basis of the duck plague virus gC gene deletion strain CHv-ΔgC, based on the duck plague virus bacterial artificial chromosome (BAC) platform in our laboratory, the gE gene was knocked out using the traceless deletion technology to obtain gC/gE double gene deletion candidate vaccine strain CHv-ΔgC/gE. The double gene deletion strain (CHv-ΔgC/gE) constructed in this study has greatly weakened virulence, no pathogenicity to ducks, and stable genetic characteristics in vitro and in vivo. Ducks immunized with CHv-ΔgC/gE can produce neutralizing antibodies and ELISA antibody levels comparable to those of commercial duck plague attenuated vaccine immunization, and can resist 100 LD50 CHv challenge of ducks, with good immune protection effect. It has the potential to be further developed into duck plague gC/gE double gene deletion, marked attenuated vaccine.